2022
DOI: 10.3389/fimmu.2022.927132
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Treatment of Glioblastoma by Chimeric Antigen Receptor T-Cell Immunotherapy and Possible Solutions

Abstract: Glioblastoma (GBM), one of the most lethal brain cancers in adults, accounts for 48.6% of all malignant primary CNS tumors diagnosed each year. The 5-year survival rate of GBM patients remains less than 10% even after they receive the standard-of-care treatment, including maximal safe resection, adjuvant radiation, and chemotherapy with temozolomide. Therefore, new therapeutic modalities are urgently needed for this deadly cancer. The last decade has witnessed great advances in chimeric antigen receptor T (CAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 128 publications
(189 reference statements)
0
4
0
Order By: Relevance
“…The canonical "second generation" CAR recognizes target antigen by an extracellular single chain fragment of variable region (scFv) antibody that is composed of the variable domains of the antibody heavy (VH) and light (VL) chains tethered together by a short flexible linker in the order VH-VL or VL-VH (16,17). A hinge region physically connects the scFv to the transmembrane domain and is usually derived from the IgG1 CH2-CH3 region, the extracellular part of CD28 or from the hinge domain of the CD8a molecule (18).…”
Section: Modifying the Carmentioning
confidence: 99%
“…The canonical "second generation" CAR recognizes target antigen by an extracellular single chain fragment of variable region (scFv) antibody that is composed of the variable domains of the antibody heavy (VH) and light (VL) chains tethered together by a short flexible linker in the order VH-VL or VL-VH (16,17). A hinge region physically connects the scFv to the transmembrane domain and is usually derived from the IgG1 CH2-CH3 region, the extracellular part of CD28 or from the hinge domain of the CD8a molecule (18).…”
Section: Modifying the Carmentioning
confidence: 99%
“…Recent advances in T-cell immunotherapy and the prominent success of CAR-T-cell therapy in treating hematological malignancies have encouraged attempts to utilize these promising novel therapeutics in treating brain malignancies [ 13 , 14 ]. Despite the challenges encountered in CAR-T-cell immunotherapy for glioma, such as tumor heterogeneity, the tumor immunosuppressive microenvironment, and CAR-T-cell persistence, clinical trials have revealed significant potential for CAR-T-cell immunotherapy in treating glioma [ 15 ]. Some patients have experienced tumor shrinkage and an extended survival period [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the challenges encountered in CAR-T-cell immunotherapy for glioma, such as tumor heterogeneity, the tumor immunosuppressive microenvironment, and CAR-T-cell persistence, clinical trials have revealed significant potential for CAR-T-cell immunotherapy in treating glioma [ 15 ]. Some patients have experienced tumor shrinkage and an extended survival period [ 15 , 16 ]. Notably, a patient with CAR-T targeting the antigen IL13Ra2 achieved complete remission for up to 7.5 months, marking the first instance of CAR-T treatment achieving complete remission in a solid tumor [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…GBM is the most malignant tumour in adults, accounting for 48.6% of all malignant primary central nervous system tumors. 1 Although comprehensive treatment regimens, such as surgery, immunotherapy, and targeted therapy have been applied in clinical practice, the prognosis of patients with GBM is still poor. 2 Clinical studies have shown that the five-year survival rate is less than 10%, and the median survival time is less than 15 months.…”
Section: Introductionmentioning
confidence: 99%